The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.nimb.2019.04.067
|View full text |Cite
|
Sign up to set email alerts
|

Elongation mechanism of the ion shaping of embedded gold nanoparticles under swift heavy ion irradiation

Abstract: The elongation process under swift heavy ion irradiation (74 MeV Kr ions) of gold NPs, with a diameter in the range 10-30 nm, and embedded in a silica matrix has been investigated by combining experiment and simulation techniques: three-dimensional thermal spike (3DTS), molecular dynamics (MD) and a phenomenological simulation code specially developed for this study. 3DTS simulations evidence the formation of a track in the host matrix and the melting of the NP after the passage of the impinging ion. MD simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…An attempt to bridge this limitation was carried out by a new theoretical study, proposed to follow the complete shaping process for a wider range of Au NP sizes using a phenomenological simulation code based on the expansion/recrystallization mechanism observed by MD simulations [39]. As a result, it was concluded that the NP cannot completely expand into the matrix during the ion shaping process and should be limited by the time the track formation and the expansion process, suggesting that the matrix strongly resists the expansion of the Au NP afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…An attempt to bridge this limitation was carried out by a new theoretical study, proposed to follow the complete shaping process for a wider range of Au NP sizes using a phenomenological simulation code based on the expansion/recrystallization mechanism observed by MD simulations [39]. As a result, it was concluded that the NP cannot completely expand into the matrix during the ion shaping process and should be limited by the time the track formation and the expansion process, suggesting that the matrix strongly resists the expansion of the Au NP afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…A small elongation increment occurs after each impact. In a scenario supported by MD simulations 8,28 , the molten and expanding material from the NPs pushes to the underdense, molten track on top and beneath the nanoparticle on impact. Silica remains solid elsewhere when the ion trajectory intersects the NP from the center region.…”
Section: /22mentioning
confidence: 99%
“…Atomistic simulations performed by several groups have shown that NPs change shape on impacts 8,27,28,34 . On the other hand, the mere reproduction of the effect in the simulation does not unambiguously identify the underlying mechanism, and the conclusions drawn from MD simulations appear contradictory.…”
Section: /22mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 74 ] To date, there are two major mechanisms proposed for the elongation: a) synergy effects by ion hammering and NP melting, [ 75–82 ] and b) ion shaping by ion tracks. [ 83–88 ] Ion hammering was discovered by Klaumunzer in 1983 that the NP dimensions grow (shrink) perpendicular (parallel) to the ion beam direction, which has been well understood by effective‐flow temperature approach. [ 89 ] In 2003, D'Orleans et al observed the ion shaping that spherical NPs become prolate with major axis oriented parallel to the incident direction.…”
Section: Ion Beam Synthesis Of Nanoparticlesmentioning
confidence: 99%